ANALISIS PENGENDALIAN KUALITAS PRODUKSI DI PT ABC DENGAN METODE SIX SIGMA DALAM UPAYA MENGURANGI TINGKAT KECACATAN PRODUK - Handayani, Putri; Gloria Angelica; Gesang Adil Wijaksono; Singgih Rifqysae; Daffa Rosyad (KAMPUS AKADEMIK PUBLISING, 2026)
PT ABC is a pulp and paper manufacturing company that faces quality control issues in the Pulp Making 2 Unit, as indicated by the presence of defective pulp products. Based on production data from January 2024 to June 2025, out of a total production of 362,842 ADt, 16,074 ADt (4.43%) were identified as defects, including discoloration, sandy pulp, and knot-contaminated pulp. This study aims to analyze pulp quality control and identify the factors causing defects using the DMAIC approach. The results show that discoloration is the most dominant defect, followed by sandy pulp and knot contamination, with the main causes related to human, machine, material, method, and environmental factors. The consistent implementation of quality control SOPs is expected to reduce defect rates and improve pulp quality